Selection and daily occupancy of artificial retreat-sites by a declining Mediterranean island specialist, the European leaf-toed gecko Euleptes europaea. - Julie Quessada; Vincent Rivière; Marc Cheylan; Alban Guillaumet (Acta Herpetologica)
The European Leaf-toed Gecko, Euleptes europaea, a rock-dwelling nocturnal gecko characteristic of Mediterranean Islands, is facing local extinctions and population decline at the margins of its range. Population monitoring through artificial retreat-sites (ARS) was implemented on French’s Grand Rouveau and If islands to study the effects of management measures. We used Generalized Linear Models to identify: (i) the environmental variables (such as substrate, vegetation, and exposure to wind and sun) influencing the maximum number of individuals observed in ARS (studied in both islands); and (ii) the factors influencing ARS daily use (occupancy), including individual attributes such as age and weight, external temperature, and disturbance (Grand Rouveau only). The maximum number of geckos appeared to be determined by the thermal properties of ARS, as mediated by exposure to the dominant wind and sunlight, rather than by the structure of the habitat and nearby vegetation. An individual gecko’s presence in an ARS was positively related to its presence in the same ARS on the previous day and negatively related to its age, to the temperature of the previous night, and the number of days of disturbance. These results provide insights into the factors governing the selection and use of ARS by the European leaf-toed gecko and open perspectives on the use of ARS for the monitoring and conservation of this and other elusive terrestrial reptiles.